The Effect of Online Practicum Learning on Concept Understanding of UST Yogyakarta Science Student - Susanti, Susanti; Ernawati, Tias; Erlangga, Sony Yunior (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to analyze the effect of online practicum learning on students' conceptual understanding. The research method used in this research is descriptive quantitative. The population of this research is all students of science education study program who take practicum courses with a total of 90 students. The sampling technique used was random sampling with a total sample of 24 students. The research instrument used a test consisting of 8 description questions. Data analysis used the T test. The results showed that online practicum learning had a significant effect on students' understanding of concepts with a significance level of 0.00. Constraints encountered during online practicum learning are: availability of tools and materials, instability of the internet network, limited quota, quality of gadgets, and students not reading theory that is in line with the practicum material so they do not understand the purpose of the practicum. Online practicum learning can facilitate students and can adapt to current technological developments in accordance with the demands of 21st century learning.